Analisis Usability pada Website Jawa Timur Park Group dengan Heuristic Evaluation - Irsalina Khairina; Suprapto Suprapto; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
One of the dissemination media of information related to services and facilities provided by Jawa Timur Park is via the website. jawatimurparkgroup.com is one of Jawa Timur Park's official website which can be accessed by domestic travelers and foreign tourists. In disseminating information, one aspect that is preferred in the comfort of use of an information system is the usability aspect. So far there are several methods in the evaluation of one of them is a method Heuristic Evaluation. In this study, the evaluation process carried out two stages: an initial evaluation website Jawa Timur Park Group and evaluation of improvement website Jawa Timur Park Group is based on 10 principles Heuristic Evaluation, such as H1 - Visibility of system status, H2 - Macth Between System and The Real Word , H3 - User Control and Freedom, H4 - Consistency and Standards, H5 - Error Prevention, H6 - Recognition Rather Than Recall, H7 - Flexibility and Efficiency of Use, H8 - Aesthethic and Minimalist Design, H9 - Helps Users Recognize, Diagnose, and Errors recovers, and H10 - Help and Documentation. Based on the evaluation, the problems are most commonly found in the category H8 principle - Aesthethic and Minimalist Design. In addition, it is also necessary improvement and further development of the website Jawa Timur Park Group is based on a comparison between the results of the initial evaluation and a second evaluation on the improvement of the website are still many problems found.